Dendrimer-Based N-Acetyl Cysteine Maternal Therapy Ameliorates Placental Inflammation via Maintenance of M1/M2 Macrophage Recruitment - Liu, Yang; Na, Quan; Liu, Jin; Liu, Anguo; Oppong, Akosua; Lee, Ji Yeon; Chudnovets, Anna; Lei, Jun; Sharma, Rishi; Kannan, Sujatha; Kannan, Rangaramanujam M.; Burd, Irina (Frontiers in Bioengineering and Biotechnology, 2022)
Intrauterine inflammation (IUI) is the primary cause of spontaneous preterm birth and predisposes neonates to long-term sequelae, including adverse neurological outcomes. N-acetyl-L-cysteine (NAC) is the amino acid L-cysteine derivative and a precursor to the antioxidant glutathione (GSH). NAC is commonly used clinically as an antioxidant with anti-inflammatory properties. Poor bioavailability and high protein binding of NAC necessitates the use of high doses resulting in side effects including nausea, vomiting, and gastric disruptions. Therefore, dendrimer-based therapy can specifically target the drug to the cells involved in inflammation, reducing side effects with efficacy at much lower doses than the free drug. Towards development of the new therapies for the treatment of maternal inflammation, we successfully administered dendrimer-based N-Acetyl Cysteine (DNAC) in an animal model of IUI to reduce preterm birth and perinatal inflammatory response. This study explored the associated immune mechanisms of DNAC treatment on placental macrophages following IUI, especially on M1/M2 type macrophage polarization. Our results demonstrated that intraperitoneal maternal DNAC administration significantly reduced the pro-inflammatory cytokine mRNA of Il1β and Nos2, and decreased CD45+ leukocyte infiltration in the placenta following IUI. Furthermore, we found that DNAC altered placental immune profile by stimulating macrophages to change to the M2 phenotype while decreasing the M1 phenotype, thus suppressing the inflammatory responses in the placenta. Our study provides evidence for DNAC therapy to alleviate IUI via the maintenance of macrophage M1/M2 imbalance in the placenta.